Characteristics and Preferences of Chicken Meat Consumers before and during Covid-19 Pandemic in Sleman Regency - Swastanita Sri Setyanovina; Any Suryantini; Masyhuri Masyhuri (Agro Ekonomi, 2021)
People purchase and consume poultry meat to fulfill their animal protein needs. In early 2020, COVID-19 spread globally as well as in Indonesia that changes the social and economic conditions, which further affect people’s behavior in purchasing chicken meat. There are two types of this meat—broiler and free-range chicken—with different characteristics (attributes) that affect consumer preference. Consumers can choose chicken meat according to their needs and desires by considering its attributes. This study aims to determine chicken meat consumers' characteristics before and during the COVID-19 pandemic and determine the differences in consumer preferences for broilers and free-range chickens. The research was conducted in Sleman Regency from April to May 2020. The primary data collected through an electronic form from 100 respondents chosen by random sampling. The descriptive analysis examines chicken meat characteristics, and the Fishbein Multi-attribute determines consumer preference for chicken meat. The results showed that consumers continued to buy chicken meat during the COVID-19 pandemic but changed the amount of purchase and the purchase location. Two main attributes affecting consumer preferences, both for broilers and free-range chickens, are the aroma and freshness. The third attribute affecting consumer preference for broilers is the meat color, while in free-range chicken, it's the halal status.